AN ANALYSIS OF ILLOCUTIOANRY ACTS OF THE MAIN CHARACTER OF TRANSFORMERS MOVIE “DARK OF THE MOON” - Antonius Divani S. H; Lince Sihombing (State University of Medan, 2013)
ABSTRACT The objectives of this research were to find out the five types of illocutionary acts, namely: Directive, Commisives, Expressive, Assertive, Declarative and the dominant one used in Transformers”Dark of the Moon”. This research was conducted by using quantitative descriptive design. It took 735 utterances taken from the subtitle of Transformers “Dark of the Moon” which were released in June 29, 2011. The result of analyzing found five types of process were used in Transformers “Dark of the Moon”, they were: Directive, Commisive, Expressive, Assertive and Declarative. There were 735 illocutionary acts in 735 utterances. The findings of data analysis showed that the total numbers of process from the five types of illocutionary acts were: Directive is 361 (47,94%) utterances. The total number of Commisive is 39 (5,17%) utterances. The total number of Expressive is 58 (7,70%) utterances. The total number of Assertives is 294 (39,04%). And the total number of Declaratives is 1 (0,13%). It means that Directive is the most dominant type of Illocutionary Acts used in Transformers “Dark of the Moon” movie. Key Words: Speech Acts, Illocutionary Acts, Movie